A influência da apocalíptica na formação tardia dos livros de Oséias e Amós - Ghelli, Leônidas Ramos (2013)
This work is a dissertation on ancient literature, especially classical and apocalyptic prophecy, and investigates the texts of the prophets Hosea and Amos. Its hypothesis is that these texts are apocalyptic in nature. To demonstrate this, the paper is organized into three chapters. In the first chapter the characteristics of classical prophecy and apocalyptic literature are presented. It compares classical prophecy with its predecessor, oral prophecy, in order to establish its characteristics. Then apocalyptic literature is examined as the heir of both prophetic and wisdom literature, demonstrating its origin and peculiarities. In the second chapter it demonstrates the process followed in putting in final form the prophecies of Hosea and Amos. It is known that the texts of the prophets went through a long process of textual development, in which literary layers were aggregated and merged to explain, guide chronologically, unite or separate pericopes and update them liturgically. The stages of the text s development are analyzed, ranging from the oral proclamation of the prophecy until its final version in which apocalyptic passages have apparently been inserted. In the third and final chapter some passages of the books of Hosea and Amos that seem to have apocalyptic characteristics are identified for analysis and argumentation. Altogether we examine twelve citations. There are only a few, short passages with apocalyptic features, motifs and fragments. The goal of this paper is to point to the existence of these texts in order to highlight the apocalyptic influence exerted on the books of Hosea and Amos.